2014
DOI: 10.4028/www.scientific.net/amr.1064.42
|View full text |Cite
|
Sign up to set email alerts
|

Non-Destructive Testing for the Evaluation of Pozzolanic Mortar Reinforced to Corrosion

Abstract: Our work aims to studying the addition of the natural pozzolan located in Beni Saf (Algeria) at non-destructive testing for the evaluation of pozzolan mortar reinforced to corrosion. We chose to study this natural addition because of its low cost and its pozzolanic reactivity. To do this, we have carried out tests on mortars made to Portland cement CEM I 42,5 N and substituted by weight based percentages of different natural pozzolan (10%, 20% and 30%). We have measured the corrosion potential and the corrosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…The provided results are consistent with previous studies on the use of natural pozzolana and perlite in concrete production (e.g., [22]), where the addition of natural pozzolana and perlite improved certain mechanical properties and durability of blended cement. Hence, the study shows that natural perlite can be used as a partial replacement of cement for mortar production.…”
Section: Bending Strengthsupporting
confidence: 91%
See 3 more Smart Citations
“…The provided results are consistent with previous studies on the use of natural pozzolana and perlite in concrete production (e.g., [22]), where the addition of natural pozzolana and perlite improved certain mechanical properties and durability of blended cement. Hence, the study shows that natural perlite can be used as a partial replacement of cement for mortar production.…”
Section: Bending Strengthsupporting
confidence: 91%
“…The successful combination of natural pozzolana and perlite has been demonstrated in several previous studies, including the work conducted in [22], which investigated the use of these materials as partial replacements for cement in concrete. The authors showed that they can enhance the mechanical properties and durability of mortar.…”
Section: Contributionmentioning
confidence: 92%
See 2 more Smart Citations
“…De nombreux travaux de recherches ont été récemment menés sur l'utilisation de la perlite dans le domaine du génie civil. Ces études ont porté sur la caractérisation physico-chimique, mécanique (Guenanou et al, 2019;Hamadache et al, 2016;Ayed et al, 2022).et la durabilité (Chihaoui et al, 2022;El Mir., 2020). révélant la possibilité d'utilisation de cette perlite (substance d'origine volcanique) en tant qu'ajout cimentaire pouzzolanique (Chikouche et al, 2016;Chaib et al, 2018).…”
Section: Introductionunclassified